HUBUNGAN PRODUKTIVITAS KERJA DENGAN AKTUALISASI DIRI KARYAWAN WANITA DI ARIMBI TOUR AND TRAVEL - Komalasari, SE,MM, Yeyen (Jurnal Ekonomi dan Pariwisata, 2017)
ABSTRACT There is substantial evidence of a link between work productivity and self actualization in woman career related outcomes such as employee attitudes and behavior with the rapid changes occurring in the role of work in women‟s lives, this research project was designed to examine the productivity include career decision of female-dominated in gender neutral careers. The women who combined work responsibilities with the demands of motherhood experienced various personal challenges while attempting to creatively construct a lifestyle that integrated their two personal spheres of work and home. They experienced various work-home conflicts as they juggled full-time employment and child care, often maintaining a stressful and demanding schedule that allowed very little time for personal care and activities. The results is productivity of women employee influence by structural maturity and marriages not becomes such as a threat for the women productivity, the roles organization not pursued of women actualization in self, there is a weakness relationship between productivity and women actualization. These women made decisions for career advancement that required compromises and adjustment in the area of home and family responsibilities. After initial career decisions have been made, career counselors can continue to encourage successful career development by identifying sources of psychosocial support available to female clients, including professional women in community and professional organizations. Key words : productivity, women actualization, career.